Where is AI for Recognition on the Hype Curve? (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
This panel examined where “AI for recognition” currently sits on the hype curve, with a deliberate focus on practical realities rather than over-promising. The discussion brought together practitioners working at different layers of the recognition stack—from platform and workflow design to skills mapping engines and RPL toolkit development—surfacing a shared concern: AI’s potential is real, but its risks, costs, and governance demands are frequently understated. Panelists highlighted several recurring pitfalls. First, trust and reliability remain fragile: AI outputs can be inconsistent at the user-interface level, and hallucinations, timeouts, and variability can undermine confidence, especially in high-stakes recognition decisions. Second, cost and scalability emerged as a major constraint. Participants noted that many AI-enabled services remain stuck in “pilot mode” because inference and usage costs are hard to predict and difficult for smaller organizations to absorb without unsustainable pricing. Third, the panel emphasized the standards gap: recognition ecosystems struggle with inconsistent vocabularies, semantics, and data structures, complicatinginteroperability and increasing vendor lock-in risks. The conversation also pointed to broader issues of privacy, governance, migration strategies, IP/cultural appropriation, and the digital divide, particularly where AI becomes embedded into assessment and recognition processes. A key thread was the distinction between using AI against learners (as an automated judge) versus using AI to enable learners (as a support for reflection, communication, triage, and action). Examples included AI-assisted portfolio reflection prompts, guided “feed up / feed back / feed forward” processes, and the use of verifiable credentials and evidence as stronger trust markers in an era of mass-generated “perfect” resumes. The panel also explored emerging disruptions such as wearable AGI [artificial general intelligence] glasses, raising questions about point-of-need learning, authenticity, and what assessment should measure when performance is continuously augmented. Several contributors cautioned that AI adoption may amplify brittleness and control if it hardens recognition into rigid scoring systems. In response, the discussion repeatedly returned to “human-centered” guardrails, the likely persistence of humans in summative decisions (in some jurisdictions via legislation), and the need for discipline in tool selection,treating AI as one instrument among many, not the driver of the system. The session closed with a comment from Serge Ravet reframing the AI-assessment debate as potentially secondary to a larger opportunity: using AI to move people from awareness to meaningful action, making learning and contribution more visible over time—and then assessing outcomes and transformation rather than static “states” of competence. Keywords: AI in recognition and RPL, trust, reliability and evidence, cost and scalability of AI systems,standards, interoperability, and vendor lock-in, human-centered governance and assessment This abstract was AI-generated from the original recording of the session and then revised by the editors for accuracy and clarity.